2022
DOI: 10.3390/w14040563
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Arsenic on Fe-Modified Biochar and Monitoring Using Spectral Induced Polarization

Abstract: This work demonstrates the potential of Fe-modified biochar for the treatment of arsenic (As) simulated wastewater and the monitoring of adsorption in real-time. Specifically, we propose the utilization of date-palm leaves for the production of biochar, further modified with Fe in order to improve its adsorption function against inorganic pollutants, such as As. Both the original biochar and the Fe-modified biochar were used for adsorption of As in laboratory batch and column experiments. The monitoring of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…The authors [ 59 , 60 ] showed in their studies that the Fe-biochar composite has the potential to remove selenium from aqueous solutions. Similar trends were described by [ 61 , 62 ], who showed the ability of iron-modified biochar to adsorb arsenic at the level of 98%. Many researchers have described the use of modified biochars [ 7 ], including those modified with iron [ 63 , 64 ].…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…The authors [ 59 , 60 ] showed in their studies that the Fe-biochar composite has the potential to remove selenium from aqueous solutions. Similar trends were described by [ 61 , 62 ], who showed the ability of iron-modified biochar to adsorb arsenic at the level of 98%. Many researchers have described the use of modified biochars [ 7 ], including those modified with iron [ 63 , 64 ].…”
Section: Introductionsupporting
confidence: 88%
“…BC1 and BC2 composites are characterized by an O/C value ranging from 0.2 to 0.6, and therefore they can be described as moderately stable (half-life from 100 to 1000 years) [ 82 ]. The increasing O/C value indicates the increasing polarity and, at the same time, lower hydrophobicity of biochar [ 62 ]. Therefore, the BC1 composite seems to be the least hydrophobic of the tested samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations